THE EFFECT OF PERFORMING DRAMA ON STUDENTS’ PRONUNCIATION AT SMP KRISTEN YHS MAKASSAR - Talantan, Heryanto; Hamid, Restu Januarty; Sahib, Nur Faizah (THE ACADEMIC: ENGLISH LANGUAGE LEARNING JOURNAL, 2024)
This research aimed to find out whether or not the used performing drama had effect on students pronunciation. The writer used quasy experimental method which involved one class as the subject of the research. The population was VII grade students at SMP Kristen YHS Makassar. Sample in this research was class VII C which consists of 27 students. In this research the writer gathering data by given oral test in pre-test and post-test consist of 10 words to be pronounce by the students. All of the words the writer took from the script of Cinderella. Pre-test is given to find out how far the students ability before they were given treatment by performing drama. The writer gave the post test to know the students improvement after they were given treatment. The writer analyzed data to find the mean score, the different between pre-test and post-test used statistic formula. The result of the research showed that there was a significant different which gained by the students in pre-test and post-test. it can be concluded that performing drama in teaching speaking has significant effect on students’ pronunciation at SMP Kristen YHS Makassar. It can be seen from the students’ mean score of posttest which was 77 and the t-test of the students’ pronunciation achievement in posttest was higher than α (23.085 > 0.05).